2011
DOI: 10.1177/0194599811420811
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Surgical Outcomes of Uvulopalatopharyngoplasty for Obstructive Sleep Apnea Hypopnea Syndrome

Abstract: Disease severity, glucose and lipid metabolism, and Friedman OSA stage may be important predictors of surgical outcome of UPPP for OSAHS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
0
14
0
1
Order By: Relevance
“…In 2002, Friedman et al [18] developed a staging system to predict success in candidates for OSAHS surgery based on anatomic considerations; they then went on to demonstrate that the addition of a tongue base procedure (radiofrequency ablation) in stage II and III patients can have improved both objective (AHI) and subjective (Epworth Sleepiness Scale, ESS) outcomes. Although others have looked at predictors of success in OSAHS surgery [24], predictors of success in multilevel OSAHS surgery have not been forthcoming.…”
Section: Discussionmentioning
confidence: 99%
“…In 2002, Friedman et al [18] developed a staging system to predict success in candidates for OSAHS surgery based on anatomic considerations; they then went on to demonstrate that the addition of a tongue base procedure (radiofrequency ablation) in stage II and III patients can have improved both objective (AHI) and subjective (Epworth Sleepiness Scale, ESS) outcomes. Although others have looked at predictors of success in OSAHS surgery [24], predictors of success in multilevel OSAHS surgery have not been forthcoming.…”
Section: Discussionmentioning
confidence: 99%
“…While previous studies suggest responders to surgery typically have a lower BMI and AHI as well as certain anatomical features, [3][4][5][6][7][8][9] current predictive tools are not accurate enough for clinical use. For instance, surgical failure can result despite an apparently favorable preoperative anatomical milieu.…”
Section: Selecting Patients For Upper Airway Surgerymentioning
confidence: 95%
“…However, a significant number of patients who undergo surgery experience residual OSA 1,2 and predicting which patient is likely to respond to surgery is difficult. Several investigators have previously attempted to use anthropomorphic, 3 polysomnographic (PSG), 4,5 and anatomical [6][7][8][9] factors to predict success, but each of these do not have sufficient accuracy to be applied in clinical practice. 10 As such, there is significant motivation to better understand the mechanistic factors that determine surgery success and, as a result, to develop methods which reliably predict the patients who will respond favorably to upper airway surgery.…”
Section: Introductionmentioning
confidence: 99%
“…These were tonsil size, the percentage of time with oxygen saturation below 90 % (CT 90 ), and the vertical distance between the lower edge of the mandible and the lower edge of the hyoid. A similar study also identified CT 90 , lowest SaO 2 , as well as AHI as significant predictive factors of surgical outcome [13]. However, none of those studies have included the data regarding the duration of respiratory events in their analyses.…”
Section: Resultsmentioning
confidence: 90%
“…Studies regarding the prediction of success in surgical treatment of OSA mostly evaluated the anatomic and anthropometric features, as well as AHI [10][11][12][13]. Data on the interaction between the duration of respiratory events and OSA surgery are sparse, and little is known.…”
Section: Introductionmentioning
confidence: 99%